The General Education Act of 1970, a law for the modernization of Spain - Fernández Soria, Juan Manuel; Sevilla Merino, Diego (Historia y Memoria de la Educación, 2021)
The article aims to examine aspects that help to better understand the General Education Act of 1970 by analyzing the factors that made it a Law for the modernization of Spain. The defining feature of the Law was the ambition with which it sought to modernize the educational system; hence, we focus on the concept of «modernization» as well as its precedents and the modernizing axes contained in the Law. We also look at the socio-economic and political context that help to explain its creation. Given the law’s importance, the article pays special attention to the obstacles and resistance that made its genesis and application so difficult, as well as the controversies that have arisen from the reform it promoted. Finally, by way of discussion, an assessment of the law is made taking into account the aspects that make up the concept of “modernization”.